O‘QITUVCHI PSIXOLOGIYASI - Xolniyozov Xurshid Sobir o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  The  success  of  the  education  system  depends,  first  of  all,  on  the professional skills, personal qualities and psychological preparation of the teacher. The teacher  is  not  only  a  provider  of  knowledge,  but  also  a  mentor  who  shapes  the personality, influences the development of socio-moral views, and provides spiritual support to students. Therefore, modern pedagogy has turned the complex psychological study of the teacher's personality into a separate scientific direction.